Students' Legal Awareness and Copyright Compliance in Academic E-Book Usage - Muhammad Samsul Arifin (Law and Judicial Review, 2026)
Objective: This study aims to analyze the influence of students’ legal awareness on copyright compliance in the use of e-books and digital academic works within the university environment. Research Design & Methods: This study employs a quantitative approach using an explanatory research design through a cross-sectional survey. The study sample consisted of 350 students from several public universities on the island of Java, selected using stratified random sampling. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression with the aid of SPSS version 26. The independent variables consisted of legal knowledge, legal understanding, legal attitudes, and legal behavior patterns, while the dependent variable was copyright compliance. Findings: The results of the study indicate that legal awareness has a positive and significant effect on students’ legal compliance. Among the dimensions of legal awareness examined, legal knowledge and legal attitudes were found to be the most dominant factors influencing student compliance, followed by legal understanding, which also had a significant effect. Meanwhile, legal behavior tendencies did not show a significant influence on legal compliance. In general, the level of legal awareness and student compliance fell into the moderate category, with legal knowledge being the relatively lowest aspect. Contributions: This study makes a theoretical contribution to the development of the concept of legal awareness in the context of the digital academic environment and enriches the literature on copyright compliance in higher education settings in developing countries, particularly Indonesia. Practically, this study provides recommendations for universities to strengthen legal literacy and copyright protection policies within the digital academic ecosystem. Novelty: The novelty of this study lies in its specific focus on legal compliance with copyright in the use of e-books and digital academic works, as well as the modeling of legal awareness as a multidimensional construct encompassing knowledge, understanding, attitudes, and behavior within the context of higher education in Indonesia.